Insurgency, political risk, and foreign direct investment inflows in Nigeria: A sectorial analysis - Iyaji Danjuma (CBN Journal of Applied Statistics, 2021)
This study examines, among others, the effect of terrorism, political violence, corrup- tion, and religious tension on FDI inflows to the banking, construction, manufactur- ing, oil and gas, and telecommunication sectors in Nigeria. Thus, empirical models were estimated using the fully modified ordinary least squares (FMOLS) technique. The study spans from 2008Q1 to 2017Q4. Findings show that terrorism adversely affects FDI inflow to telecommunication sector, while corruption positively impacts on the oil and gas sector. Thus, this study among other things, recommends the intensification of effort in the war against terrorism and strengthening of relevant anti-graft agencies to adequately fight corruption in Nigeria in other to enhance the country's attractiveness to FDI inflow.
Keywords: F21; F23; F52; H5; 330; Corruption; foreign direct investment; fully modified ordinary least square; terrorism